Transplante e óbito em crianças e adolescentes em terapia renal substitutiva no Sistema Único de Saúde, no Brasil, de 2002 a 2014 - Celina de Faria Rezende (2023)
Introduction: Chronic kidney disease (CKD) is a serious condition that affects about 1 to 3% of children and adolescents worldwide, with congenital anomaly of the kidney and urinary tract (CAKUT) being the main cause in this population. CKD can progress to stage 5, in which the patient requires renal replacement therapy (RRT). RRT includes hemodialysis, peritoneal dialysis and kidney transplantation. Objectives: The present study describes the characteristics and outcomes of pediatric patients with chronic kidney disease (CKD) who started renal replacement therapy (RRT) by the Brazilian Unified Health System between 2002 and 2014. Methods: a retrospective cohort study was carried out using secondary data from the National Registry of Renal Replacement Therapy, which included 7,544 patients aged between 0 and 17 years and 11 months. The main outcomes evaluated were kidney transplantation and occurrence of death. Results: Patients were mostly male, white and adolescents, with a median age of 13 years. Hemodialysis was the most used RRT, with 36.5% of patients with arteriovenous fistula. In 38.4% of cases, kidney transplantation occurred, with a median follow-up time of 70 months, and 12.7% died during the follow-up period. Kidney transplantation, especially preemptive, was the main factor that reduced the risk of death. Other factors that positively influenced transplantation and survival were male sex, being from the southern region of Brazil and receiving treatment outside the macroregion of residence. Dialytic treatment presented a higher risk of death. Conclusion: Pediatric patients with CKD should be transplanted as soon as possible, preferably preemptive, and spend as little time as possible on dialysis. The epidemiology of CKD in children and adolescents is an evolving field, essential to guide public health policies and clinical practices aimed at preventing, early diagnosing and treating this complex disease.